Dyslipidemia among Children and Adolescents with Type 1 Diabetes Mellitus in Tripoli University Hospital - Omalmir Fathalla; Khadeejah Ajalal (AlQalam Journal of Medical and Applied Sciences, 2026)
Diabetes is a major risk factor for cardiovascular disease (CVD). In patients with type 1 diabetes mellitus (T1DM), atherosclerosis tends to occur earlier in life, leading to increased morbidity and mortality compared with the general population. This study aimed to describe the frequency and pattern of dyslipidemia in children and adolescents with T1DM, and its relation to glycemic control, physical activity, and duration of diabetes in Tripoli, Libya. This case-control study included 131 children and adolescents with T1DM, recruited from the diabetic clinic as the case group, and 71 healthy age- and sex-matched children and adolescents from the casualty department as the control group, all from Tripoli University Hospital. Participants underwent full history taking, clinical examination, and laboratory investigations including glycosylated hemoglobin, fasting lipid profile (triglycerides [TG], low-density lipoprotein cholesterol [LDL-C], high-density lipoprotein cholesterol [HDL-C], and total cholesterol [TC]), as well as liver enzymes. There was a statistically significant increase in the frequency of dyslipidemia among diabetic patients (40.46%). The most common type of dyslipidemia was hypertriglyceridemia (26%), followed by hypercholesterolemia (21.4%), elevated LDL-C (13%), and low HDL-C (7.6%). Interestingly, low HDL-C was slightly more frequent in the control group (8.5% vs. 7.6%). The results suggest that dyslipidemia is more common in patients with poor glycemic control, which may play a major role in the development of cardiovascular disease in this population. This study recommends that patients with T1DM undergo routine lipid profile screening, with early intervention and management to reduce long-term cardiovascular risk.